2021
DOI: 10.3389/fmicb.2021.765531
|View full text |Cite
|
Sign up to set email alerts
|

Actinobacteria From Desert: Diversity and Biotechnological Applications

Abstract: Deserts, as an unexplored extreme ecosystem, are known to harbor diverse actinobacteria with biotechnological potential. Both multidrug-resistant (MDR) pathogens and environmental issues have sharply raised the emerging demand for functional actinobacteria. From 2000 to 2021, 129 new species have been continuously reported from 35 deserts worldwide. The two largest numbers are of the members of the genera Streptomyces and Geodermatophilus, followed by other functional extremophilic strains such as alkaliphiles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(21 citation statements)
references
References 251 publications
(303 reference statements)
0
20
0
1
Order By: Relevance
“…Microbial antagonists, also known as BCAs, for plant diseases prevent infection or establishment of the pathogen in host plants to control phytopathogens (Thambugala et al, 2020). Compared to other microorganisms, actinobacteria appear to withstand harsh conditions such as high temperature, salinity, and aridity (Dion, 2008;Qin et al, 2019;Xie and Pathom-aree, 2021). Therefore, we hypothesize that rhizospheric actinobacteria secreting ACCD along with a broad spectrum of antagonistic mechanisms against F. solani can substantially reduce the detrimental effect of SDS on date palm.…”
Section: Discussionmentioning
confidence: 99%
“…Microbial antagonists, also known as BCAs, for plant diseases prevent infection or establishment of the pathogen in host plants to control phytopathogens (Thambugala et al, 2020). Compared to other microorganisms, actinobacteria appear to withstand harsh conditions such as high temperature, salinity, and aridity (Dion, 2008;Qin et al, 2019;Xie and Pathom-aree, 2021). Therefore, we hypothesize that rhizospheric actinobacteria secreting ACCD along with a broad spectrum of antagonistic mechanisms against F. solani can substantially reduce the detrimental effect of SDS on date palm.…”
Section: Discussionmentioning
confidence: 99%
“…This research demonstrated that volcanic islands are an interesting source of “rare Actinobacteria,” and many strains with cytotoxic activity could be extensively discovered from them. In future, on the one hand, new types of media and methods should be designed for the isolation of novel rare Actinobacteria ( Fang et al, 2017 ; Li et al, 2021b ; Salam et al, 2021 ; Xie and Pathom-aree, 2021 ); on the other hand, genome sequencing and analysis should be conducted to unveil a vast reservoir of biosynthetic gene clusters (BGCs) for natural products in genomes of rare Actinobacteria, which is promising for extensive mining of novel chemicals and unknown biosynthetic mechanisms ( van Bergeijk et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since desertification is universally acknowledged as a severe threat to biodiversity, converting desert soil into fertile, green ecosystems is a global goal. (Köberl et al, 2013) Deserts, being an unknown extreme ecosystem, are known to host various actinobacteria with biotechnology promises (Xie et al, 2021). These harsh environments are a potentially rich source of bacteria that produce new compounds with biological characteristics.…”
Section: Introductionmentioning
confidence: 99%